2006
DOI: 10.4049/jimmunol.176.7.3895
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Itk-Dependent Signals Required for CD4+ T Cells to Exert, but Not Gain, Th2 Effector Function

Abstract: The TCR signals for the release of CD4 effector function are poorly understood. Itk plays an essential role in Th2, but not Th1, responses. However, when Itk is required during Th2 development is unclear. We followed the fate of Itk-deficient T cells during Th2 development in vitro and in vivo using an IL-4/GFP reporter. Surprisingly, a similar frequency of itk−/− CD4+ cells differentiated and committed to the Th2 lineage as wild-type cells. However, Itk-deficient Th2 cells failed to exert effector function up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 25 publications
4
75
0
Order By: Relevance
“…ϩ T cells at least, such transcriptional enhancement is critical for effective IL-4 production by Th2 cells (29). For IL-4 therefore, NKT cells and conventional Th2 cells share a common requirement for Itk to exert effector function.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ϩ T cells at least, such transcriptional enhancement is critical for effective IL-4 production by Th2 cells (29). For IL-4 therefore, NKT cells and conventional Th2 cells share a common requirement for Itk to exert effector function.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 production can be restored in Itk-deficient Th2 effector cells by the provision of TCR signals with ionomycin (29). This result suggested that conventional CD4 ϩ T cells differentiated into Th2 cells with similar cytokine potential as WT cells but lack the appropriate activation signals to exert effector function.…”
Section: Distinct Roles For Itk In Nkt Cell Development and Effector mentioning
confidence: 92%
See 3 more Smart Citations